1891 Wis. Sess. Laws 699, ch. 123, § 2, pt. 53 - (:unkn) unknown (General Publisher, 1891)
Authorized the city to regulate and prohibit the concealed carry of any pistol, revolver, slung shot, or corss-knuckles, knuckles of lead, brass or other metal, Bowie-knife, dirk-knife, dirk, dagger, or any other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED